Revealing the Moderating Role of Organizational Support in HR Professionals’ Competencies, Willingness, and Effectiveness Relationship: Empirical Evidence From a Developing Economy - Ahmad, Aqeel; Fareed, Muhammad; Isa, Mohd Faizal Mohd; Salleh, Sri Sarah Maznah Mohd (Frontiers in Psychology, 2022)
This study explores the moderating relationship of organizational support between human resource (HR) professionals’ competencies, HR professionals’ willingness, and HR professionals’ effectiveness. HR Professionals’ competencies such as credible activist, talent manager, culture and change steward, strategy architect, business ally, and operational executor nurture HR professionals’ effectiveness. Besides, HR professionals’ willingness serves as a significant predictor of HR professionals’ effectiveness. Data were collected from a total of 183 managers from commercial banks of Pakistan. Partial least squares – structural equation modeling (PLS-SEM) is used to analyze the data and test the hypotheses. The findings from a cross-sectional survey revealed the positive and significant impact of HR professionals’ competencies and HR professionals’ willingness on HR professional’s effectiveness. Moreover, the moderating impact of organizational support was also significant among HR professionals’ competencies, HR professionals’ willingness, and HR professionals’ effectiveness relationship. The study contributes to a unique attempt in the literature of HR and organizational support in the context of the banking sector. Study implications and future directions are also discussed.